2024
DOI: 10.1590/1519-6984.256354
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review on the documented characteristics of four Reticulitermes termites (Rhinotermitidae, Blattodea) of China

Abstract: Termites are known as social insects worldwide. Presently in China 473 species, 44 genera and 4 families of termites have been reported. Of them, 111 Reticulitermes species are widely spread in different zones of China. The dispersion flight season of these Chinese Reticulitermes species are usually started from February to June, but in some regions different species are distributed, sharing their boundaries and having overlapping flight seasons. These reasons become important sources of hybridization between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 191 publications
2
2
0
Order By: Relevance
“…The embryonic stages of termite development were crucial; during this time, the embryo was served by other individuals of the colony for successful development and hatching; even larvae W1 and W2 were fed by them. These findings were generally in agreement with the results reported in previous studies [2,36,42].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The embryonic stages of termite development were crucial; during this time, the embryo was served by other individuals of the colony for successful development and hatching; even larvae W1 and W2 were fed by them. These findings were generally in agreement with the results reported in previous studies [2,36,42].…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that R. flaviceps parthenogenetically deposited a smaller number of eggs than R. aculabialis in a couple of months, while the R. flaviceps deposited lesser eggs in September than August. Our findings were consistent with those of numerous other researchers, such as Ishitani and Maekawa [42,43], who discovered that the number of eggs in early-stage female-female nests was substantially greater than that in female-male nests.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the fecundity of most eusocial insect species is extremely high as a single queen can lay hundreds of millions of eggs in a lifetime. For example, the honeybee queen, with a lifespan of about 5 years, can lay up to 200,000 eggs per year (Bodenheimer & Nerya, 1937); the queen of the army ant Eciton burchelli , with a lifespan of up to 30 years, can lay 100,000 eggs in 3 weeks (Boswell et al, 1998; Gotwald, 1995); or the queen of the termite Macrotermes subhyalinus can produce 3600 eggs in 24 h over her 20‐year lifespan (Keller, 1998; Khan et al, 2022). As a result, it appears that the reproductive individuals in eusocial insect colonies contradict the reversed reproduction–longevity trade‐off because they are both highly fecund and live longer than nonreproductives within their own colonies or solitary insect individuals.…”
Section: Eusocial Insects Contradict the Usual Fecundity/lifespan Tra...mentioning
confidence: 99%
“…When compared to non-social insects, most eusocial insect species have extremely high fecundity as a single queen can lay hundreds of millions of eggs in a lifetime. For example, the honeybee queen, with a lifespan of about 5 years, can lay up to 200,000 eggs per year (Bodenheimer and Nerya 1937); the queen of the army ant Eciton burchelli , with a lifespan of up to 30 years, can lay 100,000 eggs in three weeks (Gotwald 1995;Boswell et al 1998); or the queen of the termite Macrotermes subhyalinus can produce 3,600 eggs in 24 hours over her 20-year lifespan (Keller 1998;Khan et al 2022).…”
Section: Factors Driving Eusocial Insect Caste Lifespan Differencesmentioning
confidence: 99%